Cataract surgery in camp patients: a study on visual outcomes - Pai, SG; Kamath, SJ; Kedia, V; Shruthi, K; Pai, A (Nepalese Journal of Ophthalmology, 2011)
Aim: To assess the complications and visual outcomes associated with cataract surgery in camp patients operated at a tertiary centre. Materials and methods: In a retrospective study, 206 outreach camp patients had undergone cataract surgeries with posterior chamber intraocular lens implantation under peribulbar anesthesia over a period of 6 months. Post-operative complications on Day 1 were graded as per Oxford Cataract Treatment and Evaluation Team (OCTET) definitions. One month postoperative complications, best corrected visual acuity and refractive errors were assessed. Results: 206 eyes underwent cataract extraction with PCIOL implantation. Small incision cataract surgery (SICS) was the commonest method (78.6%) used. The most common first post-operative day complication was mild iridocyclitis (26.2%). The complications were based on OCTET definitions, and showed that 33 % had Grade I and 3.4 % had Grade II complications. The major post-operative complication after 4 weeks of surgery was posterior capsular opacity. 89.8 % of the eyes had a 4 week-post-operative best corrected visual acuity of e” 6/24. The commonest refractive error was myopia with against the rule astigmatism, seen in 86 out of 150 cases. Conclusion: High quality cataract surgery with a low rate of intra-operative complications and good visual outcome can be attained in camp patients operated in the base hospitals, thus justifying more similar screening camps to clear the vast cataract backlog. Key words: cataract surgery, eye camp, visual outcomes DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5270 Nepal J Ophthalmol 2011; 3(2): 159-164